Implementation of Online Problem-Based Learning And Nursing Students' Engagement With Modified Online Discussion With Seven Jumps (MOODS7) - Raju Kapadia; Mita Agustina; Niya Fitarsih (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2023)
The problem-Based Learning method is a problem-oriented case-based learning approach recommended for nursing education This study describes the trial application of the Problem-Based Learning learning method in the online system. The seven jumps discussion, usually done face-to-face and conventionally, in this study, was changed to an online forum by going through the same seven stages. The purpose of this study is to describe and assess the effectiveness of the online discussion process using Modified Online Discussion With Seven Jumps (MOODS7) application. The quasi-experimental method was carried out on 47 students of the DIII Nursing study program. They were given seven jumps online discussion discussing the case scenario of diabetes mellitus in the medical-surgical nursing field. The mood7 application is a medium for inputting cases, dividing small groups, and discussing via chat. Data analysis using T-Test counted every good discussion at each stage of the seven jumps. Student’s involvement was identified through the Online Student Engagement Scale. The MOODS7 obtained 273 valid chats conducted by five small groups during the discussion. The intervention group showed an increased ability to think critically in solving vignette problems with a significant mean pre-post p-value (0.001>0.005). Online discussions with the Mood7 application are suffucient to help students understand learning content better, be more active, and participate in making learning more enjoyable. The implementation of seven jumps with MOODS7 can be applied to nursing students. An online discussion is an option for increasing engagement and in accordance with the characteristics of learners in era of information and technology.